Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Language Modeling and its Personalization on Touchscreen Typing Performance

Abstract: Modern smartphones correct typing errors and learn userspecific words (such as proper names). Both techniques are useful, yet little has been published about their technical specifics and concrete benefits.One reason is that typing accuracy is difficult to measure empirically on a large scale. We describe a closed-loop, smart touch keyboard (STK) evaluation system that we have implemented to solve this problem. It includes a principled typing simulator for generating human-like noisy touch input, a simple-yet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Interfaces also need to provide users with powerful, fluid, and task-appropriate text interaction. Prominent amongst these are supporting editing and correcting [1,9,25,18], formatting of text [7], personalization [8], and context-awareness [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Interfaces also need to provide users with powerful, fluid, and task-appropriate text interaction. Prominent amongst these are supporting editing and correcting [1,9,25,18], formatting of text [7], personalization [8], and context-awareness [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, language model personalization could be incorporated and compared to the overall effect of keyboard layout on the error rate. Fowler et al showed that including language model personalization can dramatically reduce the word error rate for touch typing [Fowler et al (2015)]. …”
Section: Discussionmentioning
confidence: 99%
“…The methodology that we propose allows for the direct evaluation of gesture reconstruction error rates, or any other desired metric, by simulating realistic user interactions with a keyboard. This is similar to the approach used by Fowler et al when they simulated noisy tap typing input to estimate the effect of language model personalization on word error rate [Fowler et al (2015)]. …”
Section: Introductionmentioning
confidence: 95%
“…Word prediction has been shown to help people enter text more quickly and accurately, showing keystroke savings of up to 45% in both mobile keyboards [10] and accessibility domains [17,34,33]. Despite its utility and near-ubiquity on mobile devices, word prediction has received relatively little research attention in mobile text entry.…”
Section: Related Workmentioning
confidence: 99%
“…Typical mobile word-prediction systems use small bigram models (e.g., [10]), though one commercial predictive keyboard has implemented neural language models that are able to utilize earlier context information 1 . With the benefit of longer context, statistical language modeling has been shown to be capable of accurately predicting phrases [26,7].…”
Section: Related Workmentioning
confidence: 99%